SYSTEMATIC REVIEW OF PREDICTIVE AND ANALYTICAL MODELS IN FINANCIAL PLANNING OF ISLAMIC HOUSEHOLDS IN INDONESIA - putri vella meliyanti; Sarirotul ‘Alim; Ahmad Ibnul Karim; Agus Eko Sujianto; Amalia Nuril Hidayati (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2026)
The complexity of economic conditions increasingly drives the need for financial planning that is not only economically efficient but also compliant with Sharia principles. Approaches to financial planning are also transforming. This study aims to identify, evaluate, and synthesize predictive and analytical models in Islamic household financial planning in Indonesia, as well as formulate a more integrative conceptual model. The methods used are: Systematic Literature Review (SLR) using the PRISMA approach to Google Scholar literature on Islamic household sharia financial planning in Indonesia for the period 2020–2025. The results show that studies are still dominated by analytical approaches, such as regression and SEM/PLS, which focus on the relationships between variables such as financial literacy, religiosity, and income. Meanwhile, the use of predictive models such as forecasting and machine learning is still very limited. The main findings indicate a gap between analytical and predictive approaches in the existing literature. Therefore, this study proposes an integrative conceptual model that combines input factors, process factors, a predictive layer, and output factors to improve the effectiveness of Islamic household financial planning. This research provides theoretical contributions to the development of Islamic finance literature and practical implications for households in managing their finances more adaptively and based on Islamic values.